Exploring oscillatory motions with descriptive statistics: - Magno de Oliveira Silva; Bruno Cesar Cayres; Thiago Costa Faria; Daduí Cordeiro Guerrieri; Felipe Leite Coelho da Silva (EduSer)
This study investigates the applicability of descriptive statistics in teaching oscillatory motions through experiments. Using test bench, it was evaluated the effectiveness of a passive damper in mitigating vibrations in a single-degree-of-freedom system. The educational approach incorporated practical experimentation to reinforce the theoretical understanding of oscillatory systems and damping, aligning with active learning methodologies and critical thinking. The results demonstrate that using water as the operating fluid in the damper not only provides a practical and accessible solution for vibration attenuation but also promotes a teaching methodology that develops students' critical thinking and practical skill. This methodology, by integrating the philosophy and teaching methodologies in engineering education, proves to be replicable in other areas, promoting a more practical and interactive education.